Catalytic electrochemistry of a [NiFeSe]-hydrogenase on TiO2 and demonstration of its suitability for visible-light driven H2 production. - Reisner, E; Fontecilla-Camps, J; Armstrong, F (2009)
A [NiFeSe]-hydrogenase able to produce H(2) in the presence of O(2) forms the basis of a hybrid enzyme-TiO(2) nanoparticle system with a co-attached synthetic Ru photosensitiser for visible-light driven H(2) production at room temperature from neutral water under non-strictly anaerobic conditions on the bench.